A subjetividade da criança como chave de leitura para os entraves no processo de aprendizagem: a importância do laço educadora-criança no processo de inclusão - PAIVA, Erika dos Santos (Universidade Federal do Pará, 2025)
Being education a fundamental and necessary precept for the individual in development, the Statute of Children and Adolescents (ECA) postulates that every child and adolescent has the right to be literate. In this way, two important concepts are understood in this context: literacy, defined by the teaching of codes and letters that make up the standardized education system, and literacy skills represented by behaviors and techniques that go beyond the mastery and construction of alphabetical and spelling systems, that is, it encompasses the ability to interpret and contextualize. Although Decree 7,611/11 emphasizes the importance of specialized educational attention for children with disabilities, global developmental disorders, and high abilities, ensuring the inclusion of children with obstacles in literacy or psychological constitution in the school environment constitutes a true dilemma for most regular education teachers, as numerous questions arise about how to carry out this inclusion. Therefore, the schooling of children with learning difficulties requires active participation from teachers, the school, and, above all, the child as the protagonist with a voice in their own life story. The personalized bond between the teacher and the child in cases of obstacles in literacy allows the educator to have a new perspective on the subject's subjectivity, providing space for the recognition of the desiring subject. This transferential bond, according to psychoanalysis, is a facilitating and necessary means in the relationship between peers. In this way, the research aims to discuss, through a case study, the importance of the teacher considering, in addition to cognitive competencies, the child's subjectivity in the inclusion process. For this, as a research method, the articulation of an exploratory study with a qualitative approach was used, with the support of the qualitative clinical method that draws on psychoanalytic knowledge, such as transference and the unconscious. The study sample consisted of a therapeutic companion/teacher and a child, who was invited to participate in the research for being a user of the health service of the Center for Women's and Children's Health Care (Casmuc) and for attending Basic Education, inclusion criteria. The instrument used for data collection was APEGI (Psychoanalytic Follow-up of Children in Schools, Groups, and Institutions), composed of a semi-directed interview script and some indicators that report on the quality of the child's bond with others. The data were processed quantitatively and qualitatively and served as the basis for the construction of the clinical case. All desirable ethical recommendations for research involving human subjects were respected and followed. The case of Lucas Explorer indicates that the therapeutic companion-child bond, established through the careful gaze of the professional who made a commitment to what Lucas knew and not to what he did not know, helped support the becoming of the student as a desiring subject, allowing him to speak and have an active voice in society. In this way, the place he previously occupied, that of a child reduced to a label based on a diagnosis, can be left behind.